Neurodevelopment of amazonian infants : antenatal and postnatal exposure to methyl- and ethylmercury - Dórea, José Garrofe (2012)
Neurodevelopment as Gesell development scores (GDSs) in relation to mercury exposure in infants (<6 months of age) of one urban center and two rural villages, respectively, of ﬁsherman and cassiterite miners. Mean total hair-Hg (HHg) concentrations of infants from Itapua (3.95 ± 1.8 ppm) were statistically (P = 0.0001) diﬀerent from those of infants from Porto Velho (3.84 ± 5.5 ppm) and Bom Futuro (1.85 ± 0.9 ppm). Diﬀerences in vaccine coverage among these populations resulted in signiﬁcantly higher (P = 0.0001) mean ethylmercury (EtHg) exposure in urban infants (150 μg) than in infants from either village (41.67 μg, Itapua; 42.39 μg, Bom Futuro). There was an inverse signiﬁcant (Spearman r = −0.2300; P = 0.0376) correlation between HHg and GDS for infants from Porto Velho, but not for the rural infants from Bom Futuro (Spearman r = 0.1336; P = 0.0862) and Itapua (Spearman r = 0.1666; P = 0.5182). Logistic regression applied to variables above or below the median GDS showed that EtHg exposure (estimated probability = −0.0157; P = 0.0070) and breastfeeding score (estimated probability = −0.0066; P = 0.0536) score were signiﬁcantly associated with GDS.Conclusion. In nurslings whose mothers are exposed to diﬀerent levels of ﬁsh-MeHg (HHg), a higher score of neurological development at six months was negatively associated with exposure to additional TCV-EtHg. Results should be interpreted with caution because of unaccounted variables.